2021
DOI: 10.1111/poms.13454
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Behavior in Mode Choice: Laboratory Study of Equilibrium Transformation and Selection

Abstract: In a transportation system with multiple equilibria, coordination failure occurs when a group of travelers could achieve the efficient equilibrium but fail because they cannot coordinate their decision‐making under strategic uncertainty. This study investigated factors that might affect coordination behavior in mode choice with both positive and negative externalities. Subjects participated in a mode‐choice game in which they were required to choose between public transport and private car. Positive or negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
0
2
1
Order By: Relevance
“…It was shown that the proposed model could satisfactorily reproduce the experimental observations such as the switching rates and equilibrium flow. However, as with many other differential function-based models (Watling, 1999;He and Liu, 2012;Cantarella and Watling, 2016;He and Peeta, 2016;Kumar and Peeta, 2015;Xiao et al, 2016;Ye and Yang, 2017;Xiao et al, 2019), the proposed model converges to a stable equilibrium prediction of route flow, which deviates from the experimental observations of our experiments and those experiments in the existing studies (Iida et al, 1992;Selten et al, 2007;Zhao and Huang, 2016;Ye et al, 2018;Qi et al, 2019;Han et al, 2021). The primary reason is that those models are all deterministic, in which the network flow evolution processes are fully determined (with the probability of 1) given the initial conditions.…”
Section: Introductioncontrasting
confidence: 73%
“…It was shown that the proposed model could satisfactorily reproduce the experimental observations such as the switching rates and equilibrium flow. However, as with many other differential function-based models (Watling, 1999;He and Liu, 2012;Cantarella and Watling, 2016;He and Peeta, 2016;Kumar and Peeta, 2015;Xiao et al, 2016;Ye and Yang, 2017;Xiao et al, 2019), the proposed model converges to a stable equilibrium prediction of route flow, which deviates from the experimental observations of our experiments and those experiments in the existing studies (Iida et al, 1992;Selten et al, 2007;Zhao and Huang, 2016;Ye et al, 2018;Qi et al, 2019;Han et al, 2021). The primary reason is that those models are all deterministic, in which the network flow evolution processes are fully determined (with the probability of 1) given the initial conditions.…”
Section: Introductioncontrasting
confidence: 73%
“…The crude urban development model of the past few decades has given too much attention to the overall shape of the city layout and private car travel at the expense of developing public transport [ 1 ]. The negative effects of traffic congestion and environmental degradation brought about by the rapid growth of private cars are becoming increasingly serious [ 2 ]. This has become a focus of concern and a pressing social problem for the government to address.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the departure time choice principle of commuters and examine the theoretical assumptions, one can use the method of laboratory experiment, which is a powerful tool for studying people's choice behavior and has been widely used to examine equilibrium (Helbing et al, 2002;Gabuthy et al, 2006;Daniel et al, 2009;Rapoport et al, 2014), investigate the effect of information (van Essen et al, 2019;Qi et al, 2019;Xiao and Lo, 2016;Lu et al 2011Lu et al , 2014Ramadurai and Ukkusuri, 2007;Han et al, 2021), study traffic paradoxes (Ramadurai and Ukkusuri, 2007;Morgan et al, 2009;Rapoport et al, 2009Rapoport et al, , 2014 and assess transportation demand management measures (Hartman, 2012;Aziz et al, 2015;Rey et al, 2016).…”
Section: Introductionmentioning
confidence: 99%